2013
DOI: 10.1118/1.4816299
|View full text |Cite
|
Sign up to set email alerts
|

A method to acquire CT organ dose map using OSL dosimeters and ATOM anthropomorphic phantoms

Abstract: Purpose: To present the design and procedure of an experimental method for acquiring densely sampled organ dose map for CT applications, based on optically stimulated luminescence (OSL) dosimeters "nanoDots" and standard ATOM anthropomorphic phantoms; and to provide the results of applying the method-a dose data set with good statistics for the comparison with Monte Carlo simulation result in the future. Methods: A standard ATOM phantom has densely located holes (in 3 × 3 cm or 1.5 × 1.5 cm grids), which are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
(28 reference statements)
1
23
0
Order By: Relevance
“…The OSL dosimeter calibration and readout were detailed elsewhere. 8 Figure 3 illustrates that the agreement between the OSL measurements and the calculations was much better with the TCM tube current distribution than with the constant tube current. The latter resulted in symmetric dose distributions, largely different from the measured dose profiles.…”
Section: Resultsmentioning
confidence: 89%
“…The OSL dosimeter calibration and readout were detailed elsewhere. 8 Figure 3 illustrates that the agreement between the OSL measurements and the calculations was much better with the TCM tube current distribution than with the constant tube current. The latter resulted in symmetric dose distributions, largely different from the measured dose profiles.…”
Section: Resultsmentioning
confidence: 89%
“…Pediatric anthropomorphic phantoms have been widely used in medical dosimetry [7e30]. Experimental direct dose measurements on anthropomorphic phantoms may be considered more accurate than other methods that use simple phantoms such as a cylinders or sets of slabs [31].…”
Section: Introductionmentioning
confidence: 99%
“…5 The calibration procedure of OSLDs was detailed in a previous study which reported a method for obtaining densely sampled dose maps inside an anthropomorphic phantom with OSLDs. 40 Figure 3 showed the cross-system calibration factors of all the six Thimble chamber systems, with dosimeter system #3 being the reference system (the calibration factors for this system are one for all the kVp settings). The response varied from system to system, with the highest deviation below 0.05, and most of the deviations within 0.02.…”
Section: E Processing Of Osld Measurementsmentioning
confidence: 99%
“…These OSLDs were read twice to reduce the read-out fluctuation, and the background readings were subtracted from the average of the two readings. 40 For both nipples which were close to the boundary of the scanned region, the beam quality was considered the same as the primary beam because of overscan. 41 For the other three locations of the OSLDs, we adopted the conservative estimation that the scattered rays had the same beam qualities as the primary beams.…”
Section: E Processing Of Osld Measurementsmentioning
confidence: 99%